2012
DOI: 10.1111/j.1467-8535.2012.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

What do the numbers say? The influence of motivation and peer feedback on students’ behaviour in online discussions

Abstract: Students' non-posting behaviour in online discussions is often neglected in educational research. However, it can be a potential indicator of student learning. This study examined the relationships between motivation, peer feedback and students' posting and non-posting behaviours in online discussions in a distance learning class. Fifty-seven college students participated in collaborative learning activities through online discussions. Their posting and non-posting behavioural data were tracked automatically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 42 publications
4
50
0
5
Order By: Relevance
“…Xie and his colleagues found that posting participation (i.e., messages posted in an asynchronous online discussion system) had a significant relationship with students' motivation, which suggested that students with higher levels of intrinsic motivation had higher participation rates than those with lower levels of intrinsic motivation (Xie, DeBacker, & Ferguson, 2006;Xie, Durrington, & Yen, 2011). Further, Xie (2013) found significant influences of motivation on the frequency of students' posting and non-posting participations in asynchronous online learning. The findings also suggested that students' posting participations were more influenced by extrinsic motives (e.g., course requirements), and non-posting participations were more voluntary in nature and might be a better indicator of students' intrinsic motivation.…”
Section: Toward a Theoretical Model In Online Learning Environmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Xie and his colleagues found that posting participation (i.e., messages posted in an asynchronous online discussion system) had a significant relationship with students' motivation, which suggested that students with higher levels of intrinsic motivation had higher participation rates than those with lower levels of intrinsic motivation (Xie, DeBacker, & Ferguson, 2006;Xie, Durrington, & Yen, 2011). Further, Xie (2013) found significant influences of motivation on the frequency of students' posting and non-posting participations in asynchronous online learning. The findings also suggested that students' posting participations were more influenced by extrinsic motives (e.g., course requirements), and non-posting participations were more voluntary in nature and might be a better indicator of students' intrinsic motivation.…”
Section: Toward a Theoretical Model In Online Learning Environmentmentioning
confidence: 90%
“…Instructors and researchers can easily download students' online discussion data for analysis (i.e., time of login, total message posts, total topics read, etc.) (Xie, 2013;Xie, Miller, & Allison, 2013). At the end of the semester, the students were asked to complete a survey voluntarily.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, if allowing students to gain the problem-solving skills is the major focus, selecting the ill-structured problems (i.e., cases), in which open-ended questions have been asked and real-life events have been discussed, is recommended. In fact, it has been stated that ill-structured problems should be selected for PBL's success, because solving these kinds of problems have improved motivation and sense of community, have provided conceptual development, and have improved metacognitive skills (Savery, 2006;Xie, 2013;Xie & Bradshaw, 2008).…”
Section: Peer Assessment and Problem-solvingmentioning
confidence: 97%
“…The implementation of online peer assessment is particularly recommended, as peer assessment activities can be a useful instructional strategy in facilitating learners' participation in the learning process, particularly with online environments where the element of face-to-face communication is missing. In fact, thanks to peer assessment, it has been found that students' participation and the cohesiveness between them increased during online discussion activities (Xie, 2013). The effectiveness of implementing peer assessment in online environments has been supported by other studies as well (i.e., Cheng & Hou, 2013;Lu & Law, 2012;Tseng & Tsai, 2007;van der Pol, van der Berg, Admiraal, & Simons, 2008;Yang & Tsai, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…However, feedback need not be as formal as this. The National Research Council (2000) suggested that peer feedback can be an important source of feedback in the classroom, and Xie (2013) found that peer feedback in particular (rather than just instructor feedback) led to increased participation and engagement in online discussions. An example of peer feedback is a student replying to a peer's post by discussing the reasons why he or she agrees or disagrees.…”
Section: Feedbackmentioning
confidence: 98%